2011
DOI: 10.2478/s11536-011-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of apelin and leptin on isolated rat pulmonary arteries

Abstract: AbstractApelin (AP) and leptin (LEP) are adipokines with vasomotor actions. Taking into account the published data on the role of obesity in the development of pulmonary hypertension, we studied the implications of apelin on leptin relaxing effects on isolated rat pulmonary arteries. LEP had vasodilatatory effects on phenylephrine-precontracted rat pulmonary arteries from normal and ovalbumin-sensitized rats, but not on rats with monocrotaline-induced pulmonary hypertension. AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In agreement with literature published data, our previous results showed that LEP could have vasodilatatory effects on Phe precontracted pulmonary arteries from normal rats but not on sensitized rats (11). In this study the LEP was administered before Phe.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In agreement with literature published data, our previous results showed that LEP could have vasodilatatory effects on Phe precontracted pulmonary arteries from normal rats but not on sensitized rats (11). In this study the LEP was administered before Phe.…”
Section: Discussionsupporting
confidence: 91%
“…injection of 0.2 mL physiological saline, containing 100 mg OVA and 8 mg aluminium hydroxide. The protocol was repeated 2 weeks later (11,12). In vitro L.G.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations